A colonização de terras e a ação da Igreja Católica em Rondônia nos anos 1980 : estudo de caso sobre a formação da comunidade de Nossa Senhora Aparecida da Cachoeirinha - Ferreira, Francisco Carlos (2015)
In the context of the military regime, the president's speech Garrastazu Medici (1975) reinforced the idea of sending "men without land to land without men". The Amazon was seen as breadbasket of the world and had a demographic void, and thus can become the solution to the problems of drought and migration from the Northeast. One of the priorities of the National Security Doctrine was to occupy the territory of the Amazon. The creation of the Land Statute in 1963, the Brazilian Agrarian Reform Institute (IBRA), Agrarian Development National Institute (INDA), created in 1964, the Superintendent of the Amazon Development (SUDAM), established in 1966, would helped that speech became a reality and the construction of the Trans-Amazonian highway and the Cuiabá-Santarém in 1968. on the other hand, in the midst of so many families who arrived from various corners of the country and having to face the difficulties Rondônia, in particular offering is the Catholic Church began work in the formation of Base Communities having as guidelines the conclusions of the Second Vatican Council and the Episcopal Conferences in Latin America that emerged from it. It was in this context that was created the Community Nossa Senhora Aparecida da Cachoeirinha in 1982 and is located on Line 605, thirty five kilometers from the Parish São João Batista in the municipality of Jaru, Rondonia, Roman Catholic Diocese of Ji-Paraná, as a model that performance.